Gunshot wound causing complete spinal cord injury without mechanical violation of spinal axis: Case report with review of literature - Patil, Rahul (J Craniovertebr Junction Spine, 2015)
Penetrating spine injury (PSI) forms the third most common cause of spine injury, only next to road traffic accidents and fall. Gunshot wound (GSW) forms the major bulk of PSI. Due to easy availability of firearms and antisocial behavior, GSW which were predominant in military population is now increasingly seen in civilized society. Here, we present a detail case review of unique case of civilian GSW indirectly causing complete spinal cord injury due to shock wave generated by the bullet, along with its systematic management.